Socioeconomic Predictors of Cognition in Ugandan Children: Implications for Community Interventions - Bangirana, Paul; John, Chandy C.; Idro, Richard; Opoka, Robert O.; Byarugaba, Justus; Jurek, Anne M.; Boivin, Michael J. (PloS one, 2009)
Several interventions to improve cognition in at risk children have been suggested. Identification of key variables predicting cognition is necessary to guide these interventions. This study was conducted to identify these variables in Ugandan children and guide such interventions.A cohort of 89 healthy children (45 females) aged 5 to 12 years old were followed over 24 months and had cognitive tests measuring visual spatial processing, memory, attention and spatial learning administered at baseline, 6 months and 24 months. Nutritional status, child's educational level, maternal education, socioeconomic status and quality of the home environment were also measured at baseline. A multivariate, longitudinal model was then used to identify predictors of cognition over the 24 months.A higher child's education level was associated with better memory (p = 0.03), attention (p = 0.005) and spatial learning scores over the 24 months (p = 0.05); higher nutrition scores predicted better visual spatial processing (p = 0.002) and spatial learning scores (p = 0.008); and a higher home environment score predicted a better memory score (p = 0.03).Cognition in Ugandan children is predicted by child's education, nutritional status and the home environment. Community interventions to improve cognition may be effective if they target multiple socioeconomic variables